Friendship as ecclesial binding: a reading of St Augustine’s theology of friendship from his In Iohannis tractatus evangelium - Brown, Phillip (2020)
This work explores the notion of Augustine’s mature theology of friendship as belonging to the body of Christ—the Ecclesia Catholica. The In Iohannis euangelium tractatus provides a unique prism through which to glimpse this settled theology of friends and friendship. Friendship was a central feature of Augustine’s life; this work explores how it comes to furnish his notion of membership of the Universal Church. Within the context of the Donatists schism, in which the Tractatus is born, Augustine engages with the issues on an ecclesial as well as an emotional level. Within the Tractatus, Augustine finds an expedient account of the life of Jesus, which enables him to draw out the notion of the Church (bride of Christ) as bonded to his notion of friendship which is less noticeable from the non-Johannine New Testament canon. Within Augustine’s polemic, he reveals and exploits the notion that belonging to the Church is a belonging to the Body of Christ which constitutes the whole Christ (Totus Christus) as central to his entire notion of love. Upon this ecclesial foundation, Augustine weaves within it his trinitarian principles which undergird this notion of the Church, in order to appeal to his listeners to value membership and for others to belong. Augustine through this polemic, seeks to enfranchise his listeners in becoming active signs of God’s unity on earth as friends of Christ as common members through his own body—the Church.